Knowledge of Accredited Social Health Activists in India: a systematic review and meta analysis of evidence drawn from primary studies published between 2005 and 2022 - Shambhavi Singh; Bhaskar Tiwary; Manish Barik; Hemlata Arora; Sruthi Susan Abraham; Piyusha Majumdar; Daliya Sebastian; Svea Closser (BMC Health Services Research)
Abstract Background Since the inception of the ASHAs in the year 2005, their work horizons have increased from Reproductive, Maternal, Newborn, Child, and Adolescent health (RMNCH + A), Communicable and Non-Communicable Diseases (CD & NCD) to oral health, ophthalmologic care, and other supportive community level healthcare services. The present literature lacks comprehensive understanding and synthesis of domain-wise knowledge of ASHAs and the factors affecting their knowledge. Therefore, this study aimed to synthesize and collate the relevant evidence to understand the overall knowledge of ASHAs. Methods This systematic review and meta-analysis sourced literature from Google Scholar, PubMed, and Web of Science. Of the 1062 articles identified, 37 articles were selected for narrative synthesis and meta-analysis which focused on knowledge of ASHAs. In meta-analysis, pooled prevalence was estimated using the random effect model. Meta-analysis was performed using the statistical software R version. 3.6.1 for Microsoft Windows. Results The overall pooled prevalence of knowledge regarding maternal, neonatal/child health, communicable, and non-communicable diseases among ASHAs was 62%, 69%, 62%, and 73%, respectively. The level of education, years of experience, inadequate supervision, and training were the factors affecting their knowledge and subsequently its translation into practices within the community. The review also evidenced variation of knowledge among ASHAs across domains and geographical regions of India. Conclusion The systematic review and meta-analysis highlight that ASHAs have proven to be indispensable assets to India’s healthcare system with their strengths lying in maternal and child health programs. To further enhance their impact, it is imperative to invest in areas where they lack knowledge such as disease surveillance, and preventive healthcare. Empowering ASHAs with necessary resources, and training will not only enhance their capabilities but also contribute to the overall improvement of the healthcare system in India.